2009
DOI: 10.1152/ajpregu.00006.2009
|View full text |Cite
|
Sign up to set email alerts
|

Effects and mechanisms of gastrointestinal electrical stimulation on slow waves: a systematic canine study

Abstract: Sun Y, Song GQ, Yin J, Lei Y, Chen JDZ. Effects and mechanisms of gastrointestinal electrical stimulation on slow waves: a systematic canine study. Am J Physiol Regul Integr Comp Physiol 297: R1392-R1399, 2009. First published August 26, 2009 doi:10.1152/ajpregu.00006.2009.-The aims of this study were to determine optimal pacing parameters of electrical stimulation on different gut segments and to investigate effects and possible mechanisms of gastrointestinal electrical stimulation on gut slow waves. Twelve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
(39 reference statements)
1
18
0
Order By: Relevance
“…However, only a few studies have investigated the effects of multilocular ES in multiple parts of the GI tract in animals or humans. [11][12][13] To address a broad spectrum of GI motility disorders as well as specific requirements of individual patients, interacting active implants distributed along the GI tract are needed. Multilocular sensing of GI activity will be the basis for adaptive modulation of complex physiological functions.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few studies have investigated the effects of multilocular ES in multiple parts of the GI tract in animals or humans. [11][12][13] To address a broad spectrum of GI motility disorders as well as specific requirements of individual patients, interacting active implants distributed along the GI tract are needed. Multilocular sensing of GI activity will be the basis for adaptive modulation of complex physiological functions.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric pace‐making activity was recorded by a special Biopac amplifier (Acqknowledge, EOG 100A; Biopac Systems, Inc Santa Barbara, CA) with a frequency range of 0.016‐30 Hz via the implanted serosal electrodes. The signal was offline analyzed using a special spectral analysis software package (Ningbo MedKinetic Inc, Ningbo, Zhejiang, China) and following parameters were derived: percentage of bradygastria (percentage of time during which the dominant frequency of the gastric slow wave was in the range of 0.5‐4.0 cycles/min (cpm), percentage of normal slow waves (4.0‐6.0 cpm) and the percentage of tachygastria (6.0‐12.0 cpm) . As seen in Figure , the gastric slow wave recording was of a high signal to noise ratio without major noises.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that IES with long pulses (pulse width >50 ms) entrains intestinal slow waves and normalizes intestinal dysrhythmia (54). Whereas intestinal slow wave dysrhythmia can be reliably and consistently improved with IES or intestinal pacing, conventional IES with long pulses has not improved intestinal contractions.…”
Section: Intestinal Electrical Stimulation and Motilitymentioning
confidence: 99%